The hazard of carbapenemase (OXA-181)-producing Escherichia coli spreading in pig and veal calf holdings in Italy in the genomics era: Risk of spill over and spill back between humans and animals - Carfora, Virginia; Diaconu, Elena Lavinia; Ianzano, Angela; Di Matteo, Paola; Amoruso, Roberta; Dell'Aira, Elena; Sorbara, Luigi; Bottoni, Francesco; Guarneri, Flavia; Campana, Laura; Franco, Alessia; Alba, Patricia; et al. (Frontiers in Microbiology, 2022)
Carbapenemase-producing Enterobacterales (CPE) are considered a major public health issue. In the frame of the EU Harmonized AMR Monitoring programme conducted in Italy in 2021, twenty-one epidemiological units of fattening pigs (6.98%; 95% CI 4.37-10.47%; 21/301) and four epidemiological units of bovines <12 months (1.29%; 95% CI 0,35- 3,27%, 4/310) resulted positive to OXA-48-like-producing E. coli (n=24 OXA-181, n=1 OXA-48). Whole Genome Sequencing (WGS) for in-depth characterization, genomics and cluster analysis of OXA-181-(and one OXA-48) producing E. coli isolated, was performed. Tracing-back activities at: a) the fattening holding of origin of one positive slaughter batch, b) the breeding holding and c) one epidemiologically related dairy cattle holding, allowed detection of OXA-48-like-producing E. coli in different units and comparison of further human isolates from faecal samples of farm workers. The OXA-181-producing isolates were multidrug resistant (MDR), belonged to different Sequence Types (STs), harboured the IncX and IncF plasmid replicons and multiple virulence genes. Bioinformatics analysis of combined Oxford Nanopore Technologies (ONT) long reads and Illumina short reads identified blaOXA-181 as part of a transposon in IncX1, IncX3 and IncFII fully resolved plasmids from 16 selected E. coli, mostly belonging to ST5229, isolated during the survey at slaughter and tracing-back activities. Although human source could be the most likely cause for the introduction of the blaOXA-181-carrying IncX1 plasmid in the breeding holding, concerns arise from carbapenemase OXA-48-like-producing E. coli spreading in 2021 in Italian fattening pigs and, to a lesser extent, in veal calf holdings.